Secondary breast angiosarcoma: A multicentre retrospective survey by the national Italian association of Breast Surgeons (ANISC). (June 2019) - Taffurelli, M.; Pellegrini, A.; Meattini, I.; Orzalesi, L.; Tinterri, C.; Roncella, M.; Terribile, D.; Caruso, F.; Tazzioli, G.; Pollini, G.; Friedman, D.; Mariotti, C.; et al.
Abstract: Background: Breast angiosarcoma is a malignant mesenchymal neoplasm, which accounts for approximately 2% of all soft tissue sarcomas. Secondary breast angiosarcoma (SBA) may be related to chronic lymphedema after a mastectomy with lymph node dissection (Stewart Treves syndrome) and previous radiotherapy for complications from breast radiation treatment. It is a very rare condition; therefore, diagnosis and management are still a challenge. Methods: The ANISC collected SBA data by means of a survey sent to all Italian breast centres in the ANISC. The clinicopathological characteristics and the management of this disease were analysed. Results: Twenty-four centres participated in this survey in which 112 cases of SBA were analysed. The median age of the women with SBA was 68.9 years and it appeared approximately 90 months after the first irradiation for breast cancer. In 92% of cases, a mastectomy was performed without axillary dissection for those patients having a high grade of SBA (74.2%). The prognosis was worse in the high-grade cases (overall survival-OS: 36 months) as compared with the low-grade cases (OS: 48 months). After a follow-up of 5 years, 50.5% of the patients were still alive. Disease-free survival (DFS) was 35 months, and there were no differences between the groups of patients with either high- or low-grade histology. Conclusions: Secondary breast angiosarcoma is a very aggressive disease associated with a short survival outcome. The surgical approach still remains an important step in the course of treatment; furthermore, an accurate histological examination is helpful in establishing the prognosis of the patient. A mastectomy is mandatory. A longer OS was observed in patients with low-grade angiosarcoma as compared to high-grade angiosarcoma (C.I. 40–57 vs. 31–41 months). Highlights: Information about Secondary angiosarcoma: frequency, clinic features, diagnosis. Collection of data from different Breast Unit in Italy to monitor the progress of this disease. Correct surgery approach about this aggressive disease. Multidisciplinary managemant and correct follow up.